1 | ||
2dx = dt ⇒ dx = | dt | |
2 |
1 | 1 | 1 | 2 | 1 | ||||||
... = | ∫√tdt = | ∫t1/2dt = | * | t3/2 = | (2x −1)3/2 + C | |||||
2 | 2 | 2 | 3 | 3 |
x | ||
∫√2x−1dx=x√2x−1−∫ | dx | |
√2x−1 |
1 | 2x−1+1 | |||
∫√2x−1dx=x√2x−1− | ∫ | dx | ||
2 | √2x−1 |
1 | 1 | dx | ||||
∫√2x−1dx=x√2x−1− | ∫√2x−1dx− | ∫ | ||||
2 | 2 | √2x−1 |
3 | 1 | ||
∫√2x−1dx= | (2x−1)√2x−1+C1 | ||
2 | 2 |
1 | ||
∫√2x−1dx= | (2x−1)√2x−1+C | |
3 |
5^2 | 52 |
2^{10} | 210 |
a_2 | a2 |
a_{25} | a25 |
p{2} | √2 |
p{81} | √81 |
Kliknij po więcej przykładów | |
---|---|
Twój nick | |